Removal of organochlorine pesticide (Chlorpyrifos) from Aqueous Solution by Granular Activated Carbon - Arabambi, I. O.; Ibitoye, O. S.; Ayeni, O. H.; Kolejo, O. S.; Muritala, D. S.; Oyekan, K. S. A.; Oyediji, O. T.; Ayanniyi, O. A.; Ademola, O. C.; Aremu, E. A. (Journal of Applied Sciences and Environmental Management, 2025)
The contamination of water bodies with pesticides poses significant environmental and health risks, necessitating effective remediation techniques. Hence, the objective of this paper is to investigate the removal of organochlorine pesticide (chlorpyrifos) from aqueous solution by granular activated carbon using appropriate standard procedures. Data obtained show that optimal conditions were achieved at pH6, a contact time of 60 minutes, and a temperature of 40°C, yielding a maximum adsorption efficiency of 86.9%. Adsorption kinetics conformed to the pseudo-second-order model (R² = 0.989), while equilibrium data best fitted the Langmuir isotherm (R² = 0.9987), indicating monolayer adsorption on a homogeneous surface. Thermodynamic analysis revealed the process to be spontaneous and endothermic, with negative values for Gibbs free energy (ΔG°) and enthalpy (ΔH°). These findings demonstrate the efficacy of GAC in mitigating pesticide pollution, offering a sustainable solution for water treatment applications.